The Story of My Boyhood and Youth. (University of Wisconsin Press, 1965)
John Muir--pioneer's son, naturalist, inventor extraordinaire--was one of the most fascinating and distinguished figures in American history and one of the country's best-known advocates of land preservation and the establishment of national parks. The Story of My Boyhood and Youth is the first volume of John Muir's autobiography and the only part published before he died in 1914. Muir recounts in vivid detail the three worlds of his early life: his first eleven years in Scotland; the years 1849-1860 in the central Wisconsin wilderness; and two-and-a-half most inventive years at the University of Wisconsin during that institution's infancy.